But where do I put the couch? - Michaels, Melissa, 1967-; Wood, KariAnne (Harvest House Publishers, 2019)
When you have a home decorating question, do you wish you had a team to consult? Michaels and Wood answer actual queries from their readers. With a little bit of humor and a whole lot of how-to, they provide solutions to everyday decorating dilemmas. You can do it-- once your couch is in place, of course! -- adapted from back cover